2019
DOI: 10.1504/ijtm.2019.10021161
|View full text |Cite
|
Sign up to set email alerts
|

How individuals perform customer knowledge absorption practices - a contextual approach to open innovation

Abstract: Enabling individuals to perform open innovation practices requires an in-depth analysis of the context in which those practices are enacted. However, research on the context within which open innovation is practiced, is still in its beginning. This paper develops a theoretical framework of the relationship between open innovation practices, individuals performing those practices, and context factors that enable or constrain those individuals carrying out open innovation practices. Moreover, the paper reports e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
(142 reference statements)
0
1
0
Order By: Relevance
“…SKC refers to the acquisition of knowledge that is similar to firms’ existing knowledge elements to expand the knowledge base (Dibiaggio et al, 2014). Previous studies have found that in practice, the performance of knowledge absorption will be affected by environment uncertainty (Mahringer et al, 2019), but it has not been discussed whether a firm’s knowledge coupling will improve its ability to cope with adversity.…”
Section: Introductionmentioning
confidence: 99%
“…SKC refers to the acquisition of knowledge that is similar to firms’ existing knowledge elements to expand the knowledge base (Dibiaggio et al, 2014). Previous studies have found that in practice, the performance of knowledge absorption will be affected by environment uncertainty (Mahringer et al, 2019), but it has not been discussed whether a firm’s knowledge coupling will improve its ability to cope with adversity.…”
Section: Introductionmentioning
confidence: 99%